"Mobilizing our leaders": A multi-country qualitative study to increase the representation of women in global health leadership. - Claudia T Riche; Lindsey K Reif; Natalie T Nguyen; G Rinu Alakiu; Grace Seo; Jyoti S Mathad; Margaret L McNairy; Alexandra A Cordeiro; Aarti Kinikar; Kathleen F Walsh; Marie Marcelle Deschamps; Sandy Nerette; et al. (Public Library of Science (PLoS), 2023)
Introduction Women play an essential role in health care delivery, and it is vital that they have equal representation in health leadership for equity, innovation, and the strengthening of health systems globally. Yet women remain vastly underrepresented in global health leadership positions, providing a clear example of the deeply rooted power imbalances that are central to the calls to decolonize global health. We conducted a multi-country study in Haiti, Tanzania, India, and the USA to examine gender-based challenges to career advancement for women in the global health workforce. Quantitative data on the type and prevalence of gender-based challenges has been previously reported. In this study, we analyze qualitative data collected through focus group discussions and in-depth interviews to understand women's experiences of gender-based obstacles to career advancement, their perceptions of underlying drivers, and perspectives on effective solutions. Guided by an adaptation of the Social Action Theory, we conducted focus group discussions and in-depth interviews with women at 4 major academic centers for clinical care and research in Haiti, India, Tanzania, and the United States. In total, 85 women participated in focus groups and 15 also participated in in-depth interviews. Discussions and interviews were conducted in the local language, by an experienced local facilitator unaffiliated with the participating institution, between 2017 and 2018. Discussions were recorded, transcribed, and translated. Data were analyzed by interpretive phenomenological methods for emergent themes. Three transcendent themes on gender-based challenges were identified: 1) cultural power imbalance, referring to the prevailing norms and engrained assumptions that women are less capable than men and that women's primary responsibility should be to their families; 2) institutional power imbalance, referring to the systematic gender bias upheld by existing leadership and power structures, and ranging from exclusion from career development opportunities to sexual harassment and assault; and 3) restricted agency, referring to women's limited ability to change their circumstances because of unequal cultural and institutional structures. Participants also described local, actionable solutions to address these barriers. These included: 1) formal reporting systems for sexual harassment and assault; 2) peer support and mentorship; and 3) accessible leadership training and mandatory gender equity training. Participants proposed feasible strategies to address gender-based challenges that could improve women's retention in health careers and foster their rise to leadership. Increasing the representation of women in global health leadership positions responds directly to efforts to decolonize global health and is integral to strengthening health systems and improving health outcomes for women and children worldwide.